Assessment of some analytical procedures for the examination of the enhanced biological phosphorus removal process = Ocena wybranych procedur analitycznych w badaniach procesu wzmożonego biologicznego usuwania fosforu ze ścieków - Zdybek, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Owing to the sophisticated character of modern biological wastewater treatment systems, the diagnosis of the mechanisms and interactions involved has become extremely difficult. Further difficulties in their scientific clarification can be generated by some of the analytical procedures used.
Keywords: biologiczna oczyszczalnia ścieków; oczyszczanie ścieków; wasterwater treatment; phosphorus remowal; analitical procedures; calcium; magnesium; chemical oxygent demand